(untitled) (Revista Brasileira Multidisciplinar, 2022)
Peptic ulcer, gastroesophageal reflux, ulcers induced by the use of non-steroidal anti-inflammatory drugs, Zollinger-Ellison syndrome and ulcers resulting from H. pylori infection are conditions in which disorders related to gastric acid secretion occur. Patients report pain and discomfort, in addition to the observation of severe damage to the gastric mucosa that, therefore, need to be treated. Treatments are mainly based on the use of proton pump inhibitors, which include omeprazole and esomeprazole, but despite their undeniable efficacy, they have been shown to cause severe adverse reactions, especially in conditions of prolonged use. Thus, these data point to the need for effective yet safe therapeutic options, even in conditions where chronic use is required. In this context, this study aimed to present, through a systematic review of the literature, homeopathic resources that can be used to control gastric hypersecretion, mainly aiming at presenting a therapeutic alternative to patients who require the chronic use of drugs for this purpose. Homeopathic medicines such as Nux Vomica, Phosphorus, Kali Bichromicum, Lycopodium Clavatum, Carbo Veg, Hydrastis Canadensis, Graphites and Conium maculatum have been described in the literature as efficient for these pathologies. However, this work points to the need for more clinical studies, allowing the publication of original articles, which demonstrate the effectiveness of these drugs, since, considering the studied disorder, the literature is extremely scarce and quite generic, based mainly on reviews of the literature, based only on consultation on medical matters, which despite their importance, require complementation with more current studies, increasing the reliability of homeopathy both for health professionals and for patients.